2022
DOI: 10.1002/chem.202201026
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation and Nucleophilic Quenching: Two Routes to E−X Bond Formation in Cobalt Triple‐Decker Complexes (E=As, P; X=F, Cl, Br, I)

Abstract: The oxidation of [(Cp’’’Co)2(μ,η2 : η2‐E2)2] (E=As (1), P (2); Cp’’’=1,2,4‐tri(tert‐butyl)cyclopentadienyl) with halogens or halogen sources (I2, PBr5, PCl5) was investigated. For the arsenic derivative, the ionic compounds [(Cp’’’Co)2(μ,η4 : η4−As4X)][Y] (X=I, Y=[As6I8]0.5 (3 a), Y=[Co2Cl6‐nIn]0.5 (n=0, 2, 4; 3 b); X=Br, Y=[Co2Br6]0.5 (4); X=Cl, Y=[Co2Cl6]0.5 (5)) were isolated. The oxidation of the phosphorus analogue 2 with bromine and chlorine sources yielded the ionic complexes [(Cp’’’Co)2(μ‐PBr2)2(μ‐Br)]… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Single-crystal X-ray diffraction revealed that a cobalt tricarbonyl cation stabilized by a cyclized ligand was produced (see Scheme ). To balance the charges, half a [Co 2 Br 6 ] 2– dianion is produced along with the former cation (see Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Single-crystal X-ray diffraction revealed that a cobalt tricarbonyl cation stabilized by a cyclized ligand was produced (see Scheme ). To balance the charges, half a [Co 2 Br 6 ] 2– dianion is produced along with the former cation (see Figure ).…”
Section: Resultsmentioning
confidence: 99%